The Analysis Of Motor Performance For Pitting Dabai Fruit (Canarium Odontophyllum) - Muhammad Na’im, Suhaili (Universiti Malaysia Sarawak (UNIMAS), 2023)
Dabai fruit, known for its unique flavour, has gained popularity among food enthusiasts and those interested in Sarawak cuisine. However, the lack of an available dabai fruit pitting machine poses challenges for efficient processing. This study aims to investigate the performance of motors using MATLAB to construct an effective pitting system for dabai fruit. The project objectives involve three key aspects: conducting requirement design for dabai pitting, analysing motor sizing parameters (such as power, torque, and speed) using MATLAB, and creating a conceptual framework for the dabai pitting fruit system. The absence of a dedicated dabai fruit pitting machine hinders the efficient processing of this delicacy. To address this issue, the study focuses on three main objectives. Firstly, a survey or questionnaire is undertaken to gather important criteria and specifications for the dabai fruit pitter machine, offering a comprehensive understanding of the operating needs and issues faced by the industry. Secondly, simulation techniques in MATLAB analyse and compare the efficiency of different motor types to discover the most suitable alternative for the dabai pitting system, enabling exact analysis and accurate predictions of motor performance. Additionally, the study involves the design process utilizing SOLIDWORKS software to construct a conceptual model of the dabai pitting machine, promoting comprehension and assisting in identifying potential design enhancements or modifications. The conclusions provide significant insights into the specific needs for an effective dabai pitting machine and offer a complete analysis of motor performance using MATLAB. The conceptual design acts as a practical depiction of the proposed system, giving a tangible foundation for subsequent development and execution, contributing to the progress of the dabai fruit processing sector by streamlining the pitting process and enabling improved motor selection to enhance productivity and efficiency